2015
DOI: 10.1111/bcpt.12497
|View full text |Cite
|
Sign up to set email alerts
|

First‐Trimester Pregnancy Exposure to Venlafaxine or Duloxetine and Risk of Major Congenital Malformations: A Systematic Review

Abstract: Major depressive disorder is common among women in child-bearing age, and medical treatment is subject to substantial discussions and controversies. For Selective Serotonin reuptake inhibitors, SSRIs, a vast amount of data are available. For the newer antidepressant group of serotonin and noradrenaline reuptake inhibitors, SNRIs, significantly less data are available. Following the PRISMA guideline for systematic reviews, we performed a systematic search on the risk of major congenital malformations after firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 32 publications
2
23
0
1
Order By: Relevance
“…First trimester pregnancy exposure to serotonin–noradrenaline reuptake inhibitors (SNRIs) such as venlafaxine and duloxetine which—like tapentadol—include the NRI mechanism of action have been reviewed for major congenital malformations [30]; there was no increased risk with venlafaxine treatment and no clinically important risk with duloxetine. Venlafaxine was also judged as relatively safe during pregnancy (relating to major malformations) but the authors could not draw a definite conclusion regarding breastfeeding [31].…”
Section: Resultsmentioning
confidence: 99%
“…First trimester pregnancy exposure to serotonin–noradrenaline reuptake inhibitors (SNRIs) such as venlafaxine and duloxetine which—like tapentadol—include the NRI mechanism of action have been reviewed for major congenital malformations [30]; there was no increased risk with venlafaxine treatment and no clinically important risk with duloxetine. Venlafaxine was also judged as relatively safe during pregnancy (relating to major malformations) but the authors could not draw a definite conclusion regarding breastfeeding [31].…”
Section: Resultsmentioning
confidence: 99%
“…Serotonin has an important role in embryonic development, particularly of the neural tube and the heart . There are now data on more than 50,000 newborns exposed to SSRIs in utero, which collectively does not suggest an overall increased risk for congenital malformations . There is ongoing debate about the risk for cardiovascular malformations with first‐trimester use of SSRIs, but any increase in absolute risk is likely clinically insignificant and may be associated with particular SSRIs such as paroxetine .…”
Section: Methodsmentioning
confidence: 99%
“…A small number of studies have evaluated outcomes following SNRI (venlafaxine or duloxetine) use in pregnancy and have found no major teratogenic effects . Two recent systematic reviews found no association between first trimester exposure to venlafaxine and an increased risk for major congenital malformations . Conversely, studies have found a possible association with an increased risk for some perinatal complications, including a withdrawal syndrome with venlafaxine use in the third trimester .…”
Section: Methodsmentioning
confidence: 99%
“…Exposure in utero to selective serotonin reuptake inhibitors (SSRIs) and other antidepressants has been associated with birth defects, prematurity, small for gestational age, low birth weight, poor neonatal adaptation syndrome, gestational hypertension, and preeclampsia, although not all studies support these findings . Antidepressant medication during pregnancy may affect early brain development in humans as it has been seen in animals .…”
Section: Introductionmentioning
confidence: 99%
“…Exposure in utero to selective serotonin reuptake inhibitors (SSRIs) and other antidepressants has been associated with birth defects, 4,5 prematurity, 6 small for gestational age, 7 low birth weight, 8 poor neonatal adaptation syndrome, 9 gestational hypertension, 10 and preeclampsia, 11 although not all studies support these findings. [12][13][14][15] Antidepressant medication during pregnancy may affect early brain development in humans 16,17 as it has been seen in animals. [18][19][20] Disturbances in fetal brain development by antidepressant use in pregnancy could lead to an increased susceptibility to autism and attention deficit disorders in children.…”
Section: Introductionmentioning
confidence: 99%